Factors That Influence Nonprofit Sector Employees’ Motivation: A Case Study from Egypt - Miry, Nada Shaaban (AUC Knowledge Fountain, 2021)
The issue of employee motivation received much attention in the last few decades. That attention came from its significant practical and theoretical role in the field of management. To understand how motivation influences employees’ behavior, we have to know that every employee is motivated differently based on their preferences and characteristics. Therefore, it is essential to discover individual motivation factors for each employee. This study examines the factors that stimulate employees’ motivation and explain how to use those motivational factors to improve employees’ performance and engagement. It focuses on three non-profit organizations in Egypt and provides empirical evidence of the link between the motivation and selected variables, which are the style of leadership, the reward system, and the organizational climate. A purposive sampling approach was adopted to collect data from administrative and technical staff members. The data were collected using the qualitative method by interviewing twelve participants from the professional and managerial levels at three non-profit organizations in Egypt. The findings showed that career growth, equitable pay and benefits, leadership style, and policies and procedures positively impact employees’ motivation. Based on the findings of this study, the recommendations are to give more attention to the professional growth opportunity through using the succession plan technique to fill in the managerial role within the organization, which in turn helps in remapping the leadership style to a more impactful tool to increase motivation and engagement. Organizations can also adopt some strategies to boost their employees’ motivation, from creating a positive workplace environment, opening a communication channel between employees and senior management, and creating more flexible and competitive policies and procedures that ensure equitable pay and benefits.